STRATEGI KOMUNIKASI RR PRO 2 DALAM MEMPERTAHANKAN MINAT DENGAR REMAJA DI KOTA DENPASAR - Akmalina, Nur -; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2025)
RRI Pro 2 is a state-owned radio company whose broadcasts are intended for the benefit of all levels of society throughout the territory of the Unitary State of the Republic of Indonesia. Seeing that there are so many commercial radio companies that exist, requires every radio company in Bali, especially the city of Denpasar, to compete in attracting and maintaining listening interest. The competition that is so visible between radio companies is by vying to present the best broadcast programs. The purpose of this research is to find out how the communication strategy used by RRI Pro 2 in maintaining the listening interest of adolescents in the city of Denpasar. The method that the writer uses in this research is Descriptive Qualitative to describe the facts about the phenomenon. Based on data obtained from interviews and documentation that in maintaining listening interest is in accordance with the communication strategy through several aspects carried out by RRI Pro 2 Denpasar, namely by utilizing social media technology such as Instagram and YouTube, broadcasting on air & off air, how broadcasters in broadcast content. Meanwhile, regarding the success of the communication strategy through Laswell's theory, Laswell managed to maintain his listening interest through four important elements of Laswell's formula, namely knowing the audience, composing messages, determining methods, selection and use of media.